The Role of Regional Governments in Developing MSMEs Post-Covid 19 - Maretha Berlianantiya; Yahya Reka Wirawan (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2023)
Abstract— The COVID-19 pandemic that has hit Indonesia for almost two years and policies to reduce the spread of the COVID-19 pandemic have resulted in a decline in the regional economy, as happened in Madiun City. MSMEs, which are expected to be a solution during a crisis, are also affected by the PSBB and PPKM policies. When the Covid case declined, the local government of Madiun City developed MSMEs so that the economy of Madiun City recovered. This study aims to find out (1) How were local government policies for SMEs before the covid pandemic; (2) What is the impact of MSME local government policies in the post-Covid Pandemic. The research method used is descriptive qualitative research method. The steps are carried out with the triangulation technique. The results of the research (1) The Madiun City Government makes regulations to support MSMEs and provides training to MSME actors (2) The development of 27 MSME stalls is focused on growing a local-based economy in each kelurahan. Keywords— Local government policies, MSMEs